Global civil society : an answer to war - Kaldor, Mary (Cambridge, UK : Polity Press, 2003)
Mary Kaldor argues that the terms 'civil society' and 'global' are interlinked and reflect transformations in an increasingly globalized world.
The meanings of global civil society -- The discourse of civil society -- The ideas of 1989 : the origins of the concept of global civil society -- Social movements, NGOs and networks -- Globalization, the state and war -- September 11 : the return of the 'outside'?
Includes bibliographical references (pages 161-179) and index.
Keywords: Civil society; Globalization; Mondialisation; social theory; war; peace; State; democracy; terrorism; mouvement social; developed countries